If f(x) = 2x – 6 and dx) = 3x + 9, find (f – g(x). O A. (f- g)(x) = -x- 15 O B. (f- g)(x) = x + 15 O C. (f- g)(x) = -x+ 3<

Question

If f(x) = 2x – 6 and dx) = 3x + 9, find (f – g(x).
O A. (f- g)(x) = -x- 15
O B. (f- g)(x) = x + 15
O C. (f- g)(x) = -x+ 3
O D. (f – g)(x) = 5x + 3

in progress 0
Gerda 1 year 2021-09-01T19:11:36+00:00 1 Answers 1 views 0

Answers ( )

    0
    2021-09-01T19:12:40+00:00

    Answer:

    A

    Step-by-step explanation:

    Given that f(x) is 2x-6, and g(x) is 3x+9, all we have to do is subtract in order to find (f(x)-g(x)):

    [tex](f(x)-g(x))=\\\2x-6-(3x+9)=\\2x-6-3x-9=\\-x-15[/tex]

    [tex]\fbox{A}[/tex]

    I hope this helps! Let me know if you have any questions 🙂

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )